ANALISIS BISNIS MODEL CANVAS PADA CAFE CLEGUK: STEAK & SHAKE TAWANGMANGU - Retto Djong, Alexander Mario (Jurnal Kewirausahaan Bukit Pengharapan, 2024)
This research aims to develop a business model on Cafe Cleguk: Steak & Shake Tawangmangu using Canvas Business Model evaluation starting from the identification process then continued with SWOT analysis of 9 Business Model Canvas elements. Qualitative descriptive analysis is this research method with data collection techniques using semi-structured interviews. The results of the analysis show that there are some elements of the business model that can be developed even better. Cafe Cleguk has a clear proposition value, that is, by providing a dish of quality food service products at a friendly price. But in the growing competition among tourist sites Tawangmangu wants a cafe or restaurant to look for alternative ways in developing its business model so that it can continue to be an option. 24-hour open cafe and after-sales service can be provided to customers. Similarly, it is necessary to use technological aspects of order ordering systems such as using Gofood, Grabfood or WA business applications as well as maximizing social media. On-site orders can also use QRIS. Expansion of the service area is also required both it is the capacity of dining places and parking. Cafe Cleguk can also capture other market opportunities like making home catering, rice boxes and small meeting packages for office employees around.